Carcass traits of sheep fed banana pseudostem hay - Silveira Junior, Jose Assuncao; Pedreira, Marcio dos Santos; Carvalho da Cruz, Christian Albert; Santos-Cruz, Cristiane Leal dos; Silva Freitas, Claudio Eduardo; Oliveira, Alana Alves de; Soares, Maxwelder Santos [UNESP]; Silva, Henrique Almeida da (Univ Estadual Londrina, 2019)
The objective of this study was to evaluate carcass yield, measurements, cuts, and fat deposition of sheep fed banana pseudostem hay and Tifton 85 grass hay, with or without virginiamycin. Thirty-three uncastrated male Dorper x Santa Ines crossbred lambs at five months of age, with an average body weight of 25.00 +/- 1.95 kg, were used in a feedlot experiment. The following four diets were evaluated: Tifton 85 grass hay plus concentrate with virginiamycin, banana pseudostem hay replacing 60% of Tifton 85 grass hay plus concentrate with virginiamycin, Tifton 85 grass hay plus concentrate without virginiamycin, and banana pseudostem hay replacing 60% of Tifton 85 grass hay plus concentrate without virginiamycin. The experiment was set in a completely randomized design, in a factorial scheme, using orthogonal contrasts. The diet replacing 60% Tifton 85 grass hay by banana pseudostem hay without virginiamycin had no effect on carcass traits. The combination of virginiamycin and Tifton 85 grass hay provided increases in warm carcass weight, warm carcass yield, spine, omental and mesenteric fat deposition, and, regardless of roughage, increases in the thoracic perimeter.
Keywords: Adipose tissue; By-product; Carcass quality; Feedlot; Virginiamycin